Audit Market Structure and Competition in Australia. Issue 4 (December 2014) - Carson, Elizabeth; Redmayne, Nives Botica; Liao, Lin
<x xml:space="preserve">Abstract</x> The purpose of this review is to synthesise the existing research literature regarding the underlying structure and competitiveness of the Australian audit market. We consider the findings of Australian academic research, which has examined audit fees, non‐audit fees, market concentration, auditor choice, auditor switching and audit firm mergers. We identify the key metrics used to evaluate market structure in the academic literature and then document changes in these metrics in the Australian audit market for listed company audits during the period 2000–2011. Our analysis shows that the audit market is both highly segmented and supplier‐concentrated. We find that audit fees in Australia have increased over this period, which can be attributed to increased regulation and resulting increased audit effort needed to complete audit engagements in times of regulatory change and more recently, the global financial crisis. We provide regulators, standard setters and the profession with an evidenced‐based perspective on the market for the listed company audits, which is an important input into any future proposals to regulate the Australian audit market.